2019
DOI: 10.3389/fimmu.2019.00017
|View full text |Cite
|
Sign up to set email alerts
|

Spred2 Regulates High Fat Diet-Induced Adipose Tissue Inflammation, and Metabolic Abnormalities in Mice

Abstract: Chronic low-grade inflammation in visceral adipose tissues triggers the development of obesity-related insulin resistance, leading to the metabolic syndrome, a serious health condition with higher risk of cardiovascular disease, diabetes, and stroke. In the present study, we investigated whether Sprouty-related EVH1-domain-containing protein 2 (Spred2), a negative regulator of the Ras/Raf/ERK/MAPK pathway, plays a role in the development of high fat diet (HFD)-induced obesity, adipose tissue inflammation, meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 64 publications
0
24
1
Order By: Relevance
“…The MAPK pathway can also regulate glucose metabolism, and its activation could lead to a high level of blood glucose [8]. By inhibiting the ERK/MAPK pathway, HFD-induced obesity, adipose tissue inflammation, metabolic abnormalities, and insulin resistance would be improved [72]. Due to its pleiotropic functions, the MAPK pathway (in this case, the most significantly changed pathway) represents a potential therapeutic target for morbid obesity and the resulting metabolic problems encountered by obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK pathway can also regulate glucose metabolism, and its activation could lead to a high level of blood glucose [8]. By inhibiting the ERK/MAPK pathway, HFD-induced obesity, adipose tissue inflammation, metabolic abnormalities, and insulin resistance would be improved [72]. Due to its pleiotropic functions, the MAPK pathway (in this case, the most significantly changed pathway) represents a potential therapeutic target for morbid obesity and the resulting metabolic problems encountered by obese patients.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating evidences showed that Sprouty-related EVH1 domain-2(SPRED2) was potent inhibitors for cytokines and growth factors [23]. SPRED2 was reported to be involved in various diseases [24].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced BML-induced PF development in Spred2 −/− mice is not due to Spred2-deficiency in myeloid cells. We previously demonstrated that the production of proinflammatory mediators was up-regulated in Spred2 −/− resident or M-CSF-induced BM-derived macrophages 22,23 . Here, we examined the production of TNFα and MCP-1 by inflammatory macrophages obtained by intraperitoneal injection of thioglycolate (TG) in response to BLM or LPS.…”
Section: Spred2-deficiency Increases the Proliferation Of Bronchial Ementioning
confidence: 99%